2019
DOI: 10.3390/rs11151825
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Concentration Response to the Typhoon Wind-Pump Induced Upper Ocean Processes Considering Air–Sea Heat Exchange

Abstract: The typhoon Wind-Pump induced upwelling and cold eddy often promote the significant growth of phytoplankton after the typhoon. However, the importance of eddy-pumping and wind-driven upwelling on the sea surface chlorophyll a concentration (Chl-a) during the typhoon are still not clearly distinguished. In addition, the air-sea heat flux exchange is closely related to the upper ocean processes, but few studies have discussed its role in the sea surface Chl-a variations under typhoon conditions. Based on the cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 37 publications
1
44
0
1
Order By: Relevance
“…On the other hand, convergence inhibits upwelling within anticyclonic eddies such that subsurface water outcrops to the surface only when a typhoon initiates intensive mixing (Figure 6), while the water column is restratified rapidly after a typhoon (Figure 6b,d). Liu and Tang [59] consistently found that the typhoon-induced CHL increase differs greatly among pre-existing oceanic conditions, with cyclonic and anticyclonic eddies increasing the CHL by approximately 35% and 6%, respectively. Furthermore, the magnitude of SST cooling varies only weakly between the two types of eddies (Figure 5) because typhoon-induced mixing is dominant, while upwelling within cyclonic eddies adds to the typhoon's impact and results in greater cooling at the surface than that within anticyclonic eddies [37].…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, convergence inhibits upwelling within anticyclonic eddies such that subsurface water outcrops to the surface only when a typhoon initiates intensive mixing (Figure 6), while the water column is restratified rapidly after a typhoon (Figure 6b,d). Liu and Tang [59] consistently found that the typhoon-induced CHL increase differs greatly among pre-existing oceanic conditions, with cyclonic and anticyclonic eddies increasing the CHL by approximately 35% and 6%, respectively. Furthermore, the magnitude of SST cooling varies only weakly between the two types of eddies (Figure 5) because typhoon-induced mixing is dominant, while upwelling within cyclonic eddies adds to the typhoon's impact and results in greater cooling at the surface than that within anticyclonic eddies [37].…”
Section: Discussionmentioning
confidence: 87%
“…However, the weak background stratification condition could prohibit the wake-induced upwelling to generate strong surface thermal response [17]. In contrast, the wake-induced upwelling could still bring nutrients upward, and might enhance the primary production in the upper ocean [58,63,64]. Thus the identification of the suction/pumping process on the sub-mesoscale is meaningful to regional ecosystem dynamic studies.…”
Section: Discussionmentioning
confidence: 99%
“…After the passage of typhoon Halong, the chl-a concentration in CE increased significantly with a maximum chl-a concentration of over 0.4 mg/m 3 . the usually sufficient sunshine and strong photosynthesis after the passing of a typhoon, there can be a marked increase in the surface chl-a concentration [12,58,59]. Figure 3i shows that typhoon Neoguri increased the chl-a concentration weakly in CE and caused no changes in AE.…”
Section: Surface Responsesmentioning
confidence: 97%
“…In the tropical oceans, limited nutrient concentrations in the upper ocean are not conducive to enhancing primary productivity, which can be indicated by the variations in chl-a concentrations in phytoplankton [56,57]. Typhoon-induced upwelling and vertical mixing, which can be indicated by strong SST cooling, will bring relatively more phytoplankton and richer nutrients from the subsurface to the sea surface layer, and together with the usually sufficient sunshine and strong photosynthesis after the passing of a typhoon, there can be a marked increase in the surface chl-a concentration [12,58,59]. Figure 3i shows that typhoon Neoguri increased the chl-a concentration weakly in CE and caused no changes in AE.…”
Section: Surface Responsesmentioning
confidence: 99%